Cytoplasmic glycoengineering enables biosynthesis of nanoscale glycoprotein assemblies - Hanne L. P. Tytgat (Nature Portfolio, 2019)
Established bacterial glycoengineering platforms limit access to protein and glycan substrates. Here the authors design a cytoplasmic protein glycosylation system, Glycoli, to generate a variety of multivalent glycostructures.